2003
DOI: 10.2337/diabetes.52.7.1825
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Diabetes Increases Advanced Glycation End Products on Cardiac Ryanodine Receptors/Calcium-Release Channels

Abstract: Decrease in cardiac contractility is a hallmark of chronic diabetes. Previously we showed that this defect results, at least in part, from a dysfunction of the type 2 ryanodine receptor calcium-release channel (RyR2). The mechanism(s) underlying RyR2 dysfunction is not fully understood. The present study was designed to determine whether non-cross-linking advanced glycation end products (AGEs) on RyR2 increase with chronic diabetes and if formation of these post-translational complexes could be attenuated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 30 publications
1
89
0
1
Order By: Relevance
“…There is evidence that the intracellular concentration of Ca 2+ is reduced in cardiomyocytes of animals with experimental diabetes 23 . This occurs due to the increased activity of sodium and calcium exchanger (NCX) and decreased uptake of Ca 2+ by the sarcoplasmic reticulum (SR) via calcium ATPase of the SR (SERCA2) 15 and reduced release of Ca 2+ of SR, via ryanodine receptors (RyR2) 24 . Moreover, it is possible that the reduced density of transverse tubules in cardiomyocytes of diabetic animals can change the space between the L-type calcium channels and RyR2, which reduces the efficiency of excitation-contraction coupling 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that the intracellular concentration of Ca 2+ is reduced in cardiomyocytes of animals with experimental diabetes 23 . This occurs due to the increased activity of sodium and calcium exchanger (NCX) and decreased uptake of Ca 2+ by the sarcoplasmic reticulum (SR) via calcium ATPase of the SR (SERCA2) 15 and reduced release of Ca 2+ of SR, via ryanodine receptors (RyR2) 24 . Moreover, it is possible that the reduced density of transverse tubules in cardiomyocytes of diabetic animals can change the space between the L-type calcium channels and RyR2, which reduces the efficiency of excitation-contraction coupling 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The speed of contraction of cardiomyocytes is controlled by proteins that regulate intracellular Ca 2+ movement and the rate of ATP hydrolysis which, in turn, regulates the rate of formation of crossed bridges 21 . Cardiomyocytes of diabetic animals reduce the expression of regulatory proteins such as CaMKII, NCX, RyR2, SERCA2 and phospholamban (PLB) 5,7,15,[24][25][26] , which may delay the availability of Ca 2+ for cell contraction.…”
Section: Figure 1 -Contractile Function Of Cardiomyocytes Of Control mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, hyperglycemia also shifts the glucose glycolytic pathway into alternative pathways that are considered mediators of hyperglycemia induced cellular injury (26). The damage resulting from hyperglycemia includes elevation of advanced glycation end products (AGEs), hexosamine and polyol pathway, activation of beta 2 isoform PKC and alteration of myocardial structure and function (41)(42)(43)(44)(45)(46)(47). In addition, it has been suggested that hyperglycemia is linked to altering the expression and function of both the ryanodine receptor (RyR) and sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA), and this alteration may contribute to impair myocardial systolic and diastolic function (26).…”
Section: Hyperglycemiamentioning
confidence: 99%
“…Diabetic cardiomyopathy has been diagnosed in clinical and animal diabetic models without any symptom of vascular damage (2). At molecular level, these changes are probably derived from changes in expression and/or activity of various proteins involved in maintaining or regulating intracellular calcium homeostasis (3,4). Ryanodine receptors (RyR2) are among these groups of proteins.…”
Section: Introductionmentioning
confidence: 99%